Corporate Funding Alternatives to Support Business Growth: Case Study at PT Berlian Jasa Terminal Indonesia - Tanjung Pertiwi (Journal of International Conference Proceedings (JICP), 2019)
This study aims to analyse several alternatives of corporate funding to support business growth of PT Berlian Jasa Terminal Indonesia (BJTI). In 2019, PT BJTI faces quite a challenge, the target of increasing sales as much as 54% is far above the Internal Growth Rate and Sustainable Growth Rate of PT BJTI which is only 1.88% and 3.18%. In order to reach the expected business growth, PT BJTI requires additional funding from external sources. Taking into account the current condition of the financial performance of PT BJTI, the company needs the most effective and efficient solution so that it can support its efforts in increasing sales and at the same time, not adding unnecessary burden to PT BJTI's financial performance. An analysis of several available alternatives has been carried out, and the best alternative has been obtained. The solution to the problem of PT BJTI is to do a combination of external financing through Debt and Equity, this alternative yield lowest capital cost, amounted 9.86% and overall improve PT BJTI`s financial performance. This alternative is able to solve the problems of PT BJTI's funding needs while still maintaining its healthy performance.